The effect of progressive muscle relaxation on, anxiety, mood and dota 2 performance - Ann, Mok Hua (2020)
Esports has become a new global phenomenon throughout the attraction and growth of competitive online gaming. Competition can create high levels of stress and anxiety (Ford, Ildefonso, Jones, & Arvinen-Barrow, 2017; Hanton, Mellalieu, & Williams, 2015). Studies had proven that progressive muscle relaxation could help to reduce negative mood, decrease stress and anxiety, and enhance performance. However, there are limited studies conducted on progressive muscle relaxation for esports. This study aims to examine the effect of progressive muscle relaxation on anxiety, mood and DOTA 2 performance. There were 15 male participants recruited, age 19 to 29 years old (M = 24.80, SD = 1.474), and the total hours playing per week of the participant was from 4 to 20 hours per week, (M = 8.40, SD = 4.501). Based on a pre-test, intervention, and post-test with cross-over study design, the Gold Per Minutes (GPM) was used to measure the participant DOTA 2 performance, while the psychological aspects were measured using the Competitive State Anxiety Inventory- 2 Revised (CSAI-2R) and Brunel Mood Scale (BRUMS). The result from the mixed factorial ANOVA showed no significant difference between PMR group and control group in anxiety, mood and DOTA 2 performance. In conclusion, progressive muscle relaxation (PMR) training had no significant effect on anxiety, mood and DOTA 2 performance.